Participation and agency on an initial training course for teachers of ESOL: managing the discursive demands of the feedback on teaching conference - Watkins, Ainsley Paul (2024)
This small-scale study explores trainee participation and agency in six feedback on teaching conferences (FTCs) on a pre-service English language teacher training (TESOL) course. A requirement of the course is that trainees teach alongside their peers and the trainer, and feedback collectively on their own and each other’s performance. In the first phase of the study, the conferences were video-recorded, and transcribed. Subsequent coding and analysis of the data aimed to establish which topics were discussed, and crucially, who initiated each topic: trainee, peer-observer, or trainer. The objective was to ascertain the balance between trainee and trainer participation. The second phase consisted of a discursive exploration of five individual feedback episodes. Using elements from the field of discourse analysis (conversation analysis, speech act theory, lexical signalling), the study investigated how participants demonstrated agency by using discursive features to manage the content and trajectory of the FTC. The results of the initial topical analysis indicated that trainees took an active role by initiating 363 of the 615 topics tabled in the FTC. The qualitative phase of the study demonstrated how trainees showed further examples of agency: they made discursive choices which directed the flow of the discussion, occasionally limiting the response options available to the trainer. Trainees effectively used the opportunities afforded by the participatory structure of the FTC to ‘think aloud’, verbalizing their understanding of their teaching practice session. They did not openly contest the authority of the trainer but were agentive in other ways: they seemed to ‘flaunt’ the language norms of the FTC, emphasise personality traits, or employ humour to save face or reinforce group solidarity. The findings have several implications for ELT teacher trainers, including the need to foreground speaking rights and responsibilities in the FTC and make the ‘rules of the game’ more transparent.